Successful treatment of advanced Birt-Hogg-Dubé syndrome-associated renal cell carcinoma with sarcomatoid dedifferentiation using anlotinib combined with PD-1 inhibitor after first-line therapy failure: a case report - Liqi Yi; Chuang Li; Danfeng Xu; Le Xu (World Journal of Surgical Oncology)
Abstract Background Birt-Hogg-Dubé (BHD) syndrome is a rare autosomal dominant inherited disease caused by germline mutations in the FLCN (folliculin) gene. It often presents as skin fibrofolliculoma, pneumothorax and renal cell carcinoma. BHD syndrome-associated renal cell carcinoma usually presents with an inert course, but some cases may be associated with sarcomatoid dedifferentiation, suggesting a higher aggressiveness and poor prognosis. Case presentation A 66-year-old female patient presented with a left renal mass and underwent open radical left nephrectomy with lymph node dissection. Postoperative pathology confirmed the diagnosis of renal cell carcinoma with sarcomatoid dedifferentiation, classified as Stage IV pT4N0M0. Immunohistochemical analysis revealed vimentin (+), CD10 (+), and Ki67 (approximately 80% +), which aided in the diagnosis. Initial treatment with first-line targeted immunotherapy (axitinib plus toripalimab) was unsuccessful. Following treatment failure, genetic testing was performed and identified FLCN and BRCA2 mutations. Based on these findings, second-line therapy with anlotinib combined with toripalimab was initiated, demonstrating significant efficacy. Imaging assessments consistently indicated a partial response according to RECIST1.1 criteria. Additionally, olaparib was considered as a potential therapeutic option due to the BRCA2 mutation, and one cycle of olaparib was administered during the second-line treatment. At seven months post-operation, intra-abdominal metastatic lesions remained well-controlled, with no significant pulmonary metastasis. Routine monitoring of blood counts, liver and kidney function, thyroid function, myocardial enzymes, and cortisol levels revealed no significant adverse effects, underscoring the safety and efficacy of the treatment regimen. Conclusion This case not only reveals the complexity and treatment challenges of BHD syndrome-associated renal cell carcinoma with sarcomatoid dedifferentiation but also provides an important basis for the development of individualized treatment strategies. The successful treatment of this case suggests that targeted immunotherapy may have potential advantages in refractory cases and emphasizes the important role of gene testing in guiding individualized treatment. In the future, it is necessary to further explore the molecular mechanism of BHD syndrome-associated renal cell carcinoma and sarcomatoid renal cell carcinoma and verify the efficacy of targeted immunotherapy.